IMPLEMENTASI PENGGUNAAN QR CODE SEBAGAI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA SISWA SEKOLAH MENENGAH PERTAMA (SMP) SALAFIYAH PEKALONGAN - Lilik Riandita; Rizki Sanjaya; Nahdia Muftachina; Dewi Anggraeni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Nahdatul Ulama Indonesia, 2023)
Technology-based learning media is one of the needs for a teacher to manage and design learning media by following the current developments. Using the Quick Response Code (QR-Code) as a learning medium further empowers students to play an active role in the teaching and learning process at school. This study aims to determine the implementation of the use of the QR Code as a learning medium in Islamic Religious Education subjects. This research uses a descriptive qualitative method that utilizes qualitative data and is described descriptively. This study's results indicate that using the QR Code as a learning medium is carried out through three stages: planning, implementation, and evaluation. The use of QR codes as learning media QR Code encourages students to be more active and teachers to be more creative in designing learning.